The Environmental Integration Principle in EU Law: Normative Content and Functions also in Light of New Developments, such as the European Green Deal - Vasiliki (Vicky) Karageorgou (European Papers, 2023)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(1), 159-189 | Article | (Table of Contents) Ι. Ιntroduction. – II. The origins and the evolution of the environmental integration principle in Inter-national Law. – II. The evolution, legal status, normative content and functions of the environmental integration provision in EU Law. – III.1. The evolution of the environmental integration provision and its legal status in EU Law: towards a legal principle of environmental integration. – III.2. The addressees and scope of the principle. – III.3. The normative content of the environmental integration principle in EU Law though its association with the objective of “sustainable development”. – III.4. The functions of the principle. – ΙΙΙ.5. The insufficient operationalisation of the environmental integration principle before the adoption of the European Green Deal. – IV. Assessing the contribution of the environmental integration principle to the fundamental objective of sustainable development in light of new developments. – IV.1. The European Green Deal and the environmental integration principle: Introduction. – IV.2. The implementation of the environmental integration principle in the EU Energy and Climate policy in alignment with the EGD objectives. – IV.3. The implementation of the environ-mental integration principle in selective fields of EU Policy in alignment with the EGD objectives. – IV.4. EU Financial Instruments and the environmental integration principle. – V. Conclusions. | (Abstract) The environmental integration principle, which aims to incorporate environmental considerations into the regulatory instruments in the fields outside Environmental Law, initially emerged and evolved in International and subsequently in EU Law. Since its emergence, the environmental integration principle has been closely linked to the concept of sustainable development, given that the principle is perceived as a key instrument for its realisation. The main aim of this Article is to answer the question of whether the environmental integration principle has not only a procedural, but also a substantive meaning in EU Law and, if this question is answered in the affirmative, the question of how the substantial component of the principle can be determined. Answering this question pre-supposes not only analysing the legal status, the addressees and the regulative context of the respective provision, but also certain recent critical developments that have taken place since the adoption of the EU Green Deal. The main message underpinning this Article is that the principle also has a substantive meaning that has been reinforced since the adoption of the EU Green Deal, but often it cannot be clearly delineated. The implementation of its substantive component through the respective legal instruments can also result in conflicts with the provisions of the EU Economic Constitution.